Strategi Kepala Madrasah Dalam Meningkatkan Prestasi Akademik Siswa - Rezki Nurma Fitria; Alwasih Alwasih; Muhammad Nur Hakim (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2022)
This article aims to describe how the principal's strategy, strategic planning, and strategy implementation in improving students' academic achievement at MAN 1 Mojokerto. This study uses a qualitative approach with descriptive analysis with the subject of the deputy head of the curriculum, the head of administration and the teacher. The data collection techniques used in the form of interviews, observations and documentation studies. The validity of the data was tested by triangulation of sources and techniques. The data obtained were analyzed through data reduction, data presentation, and data verification. The results of this study indicate that 1) the principal's strategy in improving students' academic achievement is carried out by developing resources, providing scholarships to students who have achievements, giving rewards to students and teachers who take part in competitions, and developing teacher competencies according to their abilities in their fields. 2) strategic planning is carried out by compiling a strategic plan (RENSTRA), compiling a madrasah budget work plan (RKAM) and conducting a madrasah self-evaluation. 3) the implementation of the madrasa principal's strategy in improving academic achievement is carried out by compiling programs within a period of 5 years and conducting a madrasa self-evaluation every month.